Unlocking the Wanderlust: Exploring Motivations and Barriers in International Student Travel among India’s Youth - Kumar, Jeetesh; Maidullah, Sana; Bhatia, Arun (ASEAN Journal on Hospitality and Tourism, 2024)
This research examines the travel motivation and constraints experienced by international students enrolled in higher education programs in India, employing the Push-Pull Framework. Further investigates the potential factors influencing student travel and gains initial insights into their motivations, including pursuing personal rewards, escaping from personal and interpersonal environments, and the desire for interpersonal rewards, using motivation theory as a guiding framework. A sample of 300 international students studying in India was selected using purposive sampling techniques. Data was collected through a self-administered survey comprising 20 items measuring motivational factors on a five-point Likert scale, adapted from existing literature. The study provides empirical evidence of distinct patterns in international student travel, encompassing various profiles, travel motivations, and obstacles encountered by international students in India. Furthermore, the findings indicate that international students constitute a heterogeneous group of travellers engaged in travel for diverse reasons. The preference for affordable and budget-friendly modes of transportation was observed among international students. At the same time, their willingness to allocate additional funds towards a wide range of tourism offerings at their destination was evident. The implications of these findings and recommendations for future research are discussed, emphasising their significance for academic and tourism stakeholders.